Throughput Analysis of Energy Aware Routing Protocol for Real-Time Load Distribution in Wireless Sensor Network (WSN) - Tuani Ibrahim, Ahamed Fayeez; Gannapathy, Vigneswara Rao; Md Isa, Ida Syafiza; Sarban Singh, Ranjit Singh; Subramaniam, Siva Kumar (Sun Publication, 2013)
Wireless sensor network (WSNs) are self-organized systems that depend on highly distributed and scattered low cost tiny devices. These devices have some limitations such as processing capability, memory size, communication distance coverage and energy capabilities. In order to maximize the autonomy of individual nodes and indirectly the lifetime of the network, most of the research work is done on power saving techniques. Hence, we propose energy-aware load distribution technique that can provide an excellent data transfer of packets from source to destination via hop by hop basis. Therefore, by making use of the cross-layer interactions between the physical layer and the network layer thus leads to an improvement in energy efficiency of the entire network when compared with other protocols and it also improves the response time in case of network change.